Methylprednisolone Administration Following Spinal Cord Injury Reduces Aquaporin 4 Expression and Exacerbates Edema. (10th May 2017) - Cabrera-Aldana, Eibar Ernesto; Ruelas, Fernando; Aranda, Cristina; Rincon-Heredia, Ruth; Martínez-Cruz, Angelina; Reyes-Sánchez, Alejandro; Guizar-Sahagún, Gabriel; Tovar-y-Romo, Luis B.
Abstract : Spinal cord injury (SCI) is an incapacitating condition that affects motor, sensory, and autonomic functions. Since 1990, the only treatment administered in the acute phase of SCI has been methylprednisolone (MP), a synthetic corticosteroid that has anti-inflammatory effects; however, its efficacy remains controversial. Although MP has been thought to help in the resolution of edema, there are no scientific grounds to support this assertion. Aquaporin 4 (AQP4), the most abundant component of water channels in the CNS, participates in the formation and elimination of edema, but it is not clear whether the modulation of AQP4 expression by MP plays any role in the physiopathology of SCI. We studied the functional expression of AQP4 modulated by MP following SCI in an experimental model in rats along with the associated changes in the permeability of the blood-spinal cord barrier. We analyzed these effects in male and female rats and found that SCI increased AQP4 expression in the spinal cord white matter and that MP diminished such increase to baseline levels. Moreover, MP increased the extravasation of plasma components after SCI and enhanced tissue swelling and edema. Our results lend scientific support to the increasing motion to avoid MP treatment after SCI.